LABORATORY DIAGNOSIS OF HEPATITIS B - Yogarajah, Haneetha; Wiradewi Lestari, AA; Sutirta Yasa, IWP (Bali Journal of Medical and Health Sciences; vol 1no1 2013, 2013)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 H e p a t i t i s B is a l i v e r di s ea se c a used b y a virus k nown a s H e p a t i t i s B vir u s ( H B V ) a nd is a major g lo b a l h ea l t h p r o b e l m . The l i v e r is susc e p t ib l e to a wide v a ri e t y of a dv e r s e e f f e c ts ca used b y a n e x ce ss of a lcohol, d r u g s, inf e c t i ons such a s vir a l h ea l t h d e p a rtme n t. V acc i n a t i on for c hi l d re n , a doles c e nts a nd hi g h - r i sk a dul t s c ould a lso p r e v e nt h e p a t i t i s B . The p r o g nosis is v a ri a ble h e p a t i t i s, ca n ce r a nd other met a bol i c disord e rs. H e p a t i t i s B is the ca usative a g e nt a nd b e l o n g s to the h e p a d n a virid a e f a m i l y o f viru s e s. T r a n s m i ss i on of HBV virus is throu g h e x posure to in f ec ted blood a nd bo d y fluids. O n e of the i m port a nt dia g nostic c rite r ia o f He p a t i t i s B is b y p e r f o r m i n g a thorough labo ra to r y in v e st i g a t i on. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}